1987
DOI: 10.1080/03746608708685419
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fertilization on part of the Keen of Hamar Serpentine, Shetland

Abstract: Winter feeding of stock has caused eutrophication of the lower part of the Kccn of Hamar. A nutrient addition experiment is reported which shows that grass covcr of thc serpentine debris increased greatly following phosphorus fertilization. Long-term observations have shown a substantial increase in grass cover over c. 35% of the lower part of the Kccn and in one limited area the complete elimination of a rare species. It is suggested that the effects of eutrophication are likely to persist indefinitely and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This conclusion is further supported by the prevalence of leaf chlorosis, a symptom of N deficiency, of plants grown in the compost only and serpentine topsoil treatments. Several other studies in California have documented that serpentine plant communities are N-limited (Huenneke et al, 1990;Koide et al, 1988;O'Dell et al, in press;Turitzin, 1982), however, some studies from Europe, have concluded that serpentine communities there are strongly P-rather than N-limited (Carter et al, 1988;Chiarrucci et al, 1999;Nagy and Proctor, 1997). Regardless of the treatment, serpentine and granite A. millefolium accessions did not significantly differ from each other in N or P concentration, nor N:P mass ratio, suggesting that tolerance of low N and P concentrations is not a characteristic unique to plants growing on serpentine substrates, but is feature of both serpentine and nonserpentine species to nutrient-poor environments in general.…”
Section: Discussionmentioning
confidence: 94%
“…This conclusion is further supported by the prevalence of leaf chlorosis, a symptom of N deficiency, of plants grown in the compost only and serpentine topsoil treatments. Several other studies in California have documented that serpentine plant communities are N-limited (Huenneke et al, 1990;Koide et al, 1988;O'Dell et al, in press;Turitzin, 1982), however, some studies from Europe, have concluded that serpentine communities there are strongly P-rather than N-limited (Carter et al, 1988;Chiarrucci et al, 1999;Nagy and Proctor, 1997). Regardless of the treatment, serpentine and granite A. millefolium accessions did not significantly differ from each other in N or P concentration, nor N:P mass ratio, suggesting that tolerance of low N and P concentrations is not a characteristic unique to plants growing on serpentine substrates, but is feature of both serpentine and nonserpentine species to nutrient-poor environments in general.…”
Section: Discussionmentioning
confidence: 94%
“…The initial response to nutrient addition was rapid, but the total cover (still mainly due to Cochlearia in 1994) remained stable indicating that as on Rum (Looney & Proctor, 1989) and on Unst (Carter et al, 1987a; D. R. Slingsby, unpublished)…”
Section: Discussionmentioning
confidence: 99%
“…Each block included one control, -1-Ca, -I-NPK, and -l-NPKCa treatment. Fertilizer rates followed Carter et al (1987a); N was supplied as NH.NO., (100 kg ha"' N), P as NaH^PO, (50 kg ha'P), K as KCl (100 kg ha~^ K) and Ca as CaCOg (1000 kg ha"^ CaCO.^). Nitrogen, P and K were applied combined in a 600 ml solution (made up from a nearby stream) per quadrat, whereas CaCOg was applied as a powder.…”
Section: Fertilizer Applicationmentioning
confidence: 99%
“…These differences are likely due to the inherently slower growth rates of the serpentine species. Macronutrient deficiency has been diagnosed as limiting plant growth on serpentine soils of several continents, however, the limiting nutrient has varied between N, P, and Ca with apparently no collective agreement on which nutrient is most limiting (Carter et al, 1988;Chiarucci et al, 1999;Huenneke et al, 1990;Nagy and Proctor, 1997). Due to the additive plant growth responses observed with multiple macronutrient treatments in many studies, it is likely that multiple soil macronutrient deficiencies rather any single nutrient deficiency are responsible for poor plant productivity on serpentine soils globally (Chiarucci et al, 1999;Huenneke et al, 1990;Nagy and Proctor, 1997;Turitzin 1982).…”
Section: Npk Plant Nutrition and Biomass Productionmentioning
confidence: 95%